Neuromyelitis optica spectrum disorder: importance and difficulties of differential diagnosis with multiple sclerosis - M. V. Davydovskaya (Лечащий Врач)
Neuromyelitis optica spectrum disorder is a group of rare and severe immune-mediated neurological conditions. We have discussed with Maria Davydovskaya, the Deputy Chief External Experts in Neurology, the key differences of this disease from multiple sclerosis, special aspects of diagnostics and therapy, the consequences of misdiagnose, and patients support.